PENGELOLAAN KEUANGAN ENTITAS BERORIENTASI NONLABA MENURUT ISAK 35 PADA MASJID AGUNG DARUSSALAM PURBALINGGA - Setiawan, Agus Bakti; Arofah, Anastasia Anggarkusuma; Amelia, Shella Rizqi (Investama : Jurnal Ekonomi dan Bisnis, 2023)
Non-profit oriented entities are organizations that operate not for personal or specific group interests but for the benefit of the congregation or common interests. The presentation of financial statements for non-profit oriented entities is regulated by ISAK 35 standards. The objective of this research is to prepare financial statements for the Great Darussalam Mosque in Purbalingga, following the guidelines of ISAK 35 and the accounting cycle, from transaction identification to financial statement presentation. The methodology used is a qualitative descriptive approach. Data collection techniques include interviews, observations, and documentation. The research was conducted at the Great Darussalam Mosque in Purbalingga. The data sources utilized in the research consist of primary and secondary data. Primary data was obtained through interviews conducted directly with the Ta’mir Mosque's Chairman, Treasurer, and Secretary. The research findings indicate that the Great Darussalam Mosque in Purbalingga still uses a simple financial statement presentation, limited to recording cash inflows and outflows, and has not fully implemented ISAK 35. This is primarily due to the lack of human resources with accounting knowledge and the absence of accounting experts or management officials with an accounting background.